(untitled) (Journal of Supranational Policies of Education (JOSPOE), 2017)
Santos Rego, M. A. (ed.) (2016). A Investigación Educativa en Galicia (2002-2014). Vigo: Editorial Galaxia. ISBN- 978-84-9865-697-8